2019
DOI: 10.1371/journal.pone.0223437
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic and electromyographic analysis of variations in Nordic hamstring exercise

Abstract: The purpose of this study was to present and biomechanically evaluate several variations of the Nordic hamstring exercise (NHE), achieved by altering the slope of the lower leg support and by asumming different hip flexion angles. Electromyographic and 2D kinematic measurements were conducted to analyse muscle activity (biceps femoris, semitendinosus, gluteus maximus, erector spine and lateral head of the gastrocnemius), knee and hip joint torques during 6 variations of NHE. The study involved 18 adults (24.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 38 publications
4
65
0
Order By: Relevance
“…Indeed, Hegyi et al 34 have recently demonstrated that the semitendinosus‐to‐BFlh activity ratio is higher during modified NHE (ie, hip flexed at 90°) compared with the standard NHE. It should be also noted that BFlh muscle activity during standard NHE (99.7% MVC) 7 is higher than during the modified NHE (80% MVC) 5 and the glider (50%‐60% MVC) 12 . Although we have added additional loads to both exercises during the intervention, it is possible that lower activity of BFlh in these exercises could have contributed to a smaller increase in BFlh muscle thickness.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, Hegyi et al 34 have recently demonstrated that the semitendinosus‐to‐BFlh activity ratio is higher during modified NHE (ie, hip flexed at 90°) compared with the standard NHE. It should be also noted that BFlh muscle activity during standard NHE (99.7% MVC) 7 is higher than during the modified NHE (80% MVC) 5 and the glider (50%‐60% MVC) 12 . Although we have added additional loads to both exercises during the intervention, it is possible that lower activity of BFlh in these exercises could have contributed to a smaller increase in BFlh muscle thickness.…”
Section: Discussionmentioning
confidence: 99%
“…The modified NHE was performed bilaterally in a custom‐designed device with adjustable slope of the lower leg support (S2P Ltd., Science to practice). The NHE device and the modified NHE variation were previously described by Sarabon et al, 7 who showed that adding hip flexion during the NHE can lengthen hamstrings at the time of peak knee and hip torque and peak hamstring electromyographic activity. Participants were instructed to maintain 75° of hip flexion during each repetition of the NHE.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to train greater knee extension angles, either assistance with resistance bands or cable machines or an increase in the slope of the lower leg support is recommended. These methods facilitate training at more specific muscle lengths while also increasing mechanical muscle loading (especially by increasing the time under tension) [ 12 , 13 , 14 ]. In general, prevention-oriented hamstring exercises performed at longer muscle lengths have been shown to be significantly better than conventional exercises [ 15 ].…”
Section: An Evidence-based Approach To Hamstring Trainingmentioning
confidence: 99%